Water reuse: dairy effluent treated by a hybrid anaerobic biofilm baffled reactor and its application in lettuce irrigation - K. A. Santos (IWA Publishing, 2021)
There is a synergy between the large quantities of organics-rich effluents generated by the dairy industry and the continually increasing water needs for crop irrigation. In this sense, this study aimed at evaluating the effect of decreasing the hydraulic retention time (HRT) on the stability and efficiency of a hybrid anaerobic biofilm baffled reactor (HABBR) treating simulated fat- and salt-rich dairy wastewater, followed by its agricultural reuse. The reactor was monitored over 328 days, during which 72, 24, and 12 h were the hydraulic detention times. After achieving steady-state, the reactor presented organic matter removal greater than 90% and produced biogas with 41 ± 23%, 53 ± 3%, and 64 ± 12% of methane for HRTs of 72, 24, and 12 h, respectively. The best process performance was observed for an HRT of 24 h, and thus, a lettuce culture was irrigated with the treated effluent. The irrigation was performed in five different treatments, for which the amount of treated effluent added to tap water varied from 0 to 100%. Both the effluent and the harvested vegetables were evaluated for microbial contamination. Apart from the 75% effluent supply condition, there were no losses in leaf mass or area observed; instead, there was an increase of these parameters for the 25% and 50% effluent supply treatment. The use of dairy effluent treated by the HABBR allowed for microbiologically safe food production. Therefore, the process offered both potential cost reduction for fertilizers, preservation of water resources, and a renewable energy source. HIGHLIGHTS The anaerobic baffled reactor was stable during treatment of fat-rich salt dairy wastewater.; The methane content was enhanced with hydraulic retention time reduction.; The use of dairy effluent reduced the needs related to N fertilizer by up to 50%.; The use of drinking water for lettuce irrigation has been reduced by 50%.; The effluent did not present a risk of contamination in lettuce production.;